2016
DOI: 10.1161/circulationaha.115.019949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omega-3 Acid Ethyl Esters on Left Ventricular Remodeling After Acute Myocardial Infarction

Abstract: BACKGROUND Omega-3 fatty acids from fish oil have been associated with beneficial cardiovascular effects but their role in modifying cardiac structures and tissue characteristics in patients who have suffered an acute myocardial infarction (MI) while receiving current guideline-based therapy remains unknown. METHODS In a multicenter, double-blind, placebo-controlled trial, participants presenting with an acute MI were randomized 1:1 to 6-months of high-dose omega-3 fatty acids (n=178) or placebo (n=180). Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
138
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 43 publications
2
138
2
6
Order By: Relevance
“…In the light of previous reports showing that treatment with n3‐PUFAs improves left ventricular function in HF by reducing ventricular remodelling and myocardial fibrosis,8, 11 our finding is rather surprising at first. However, upon a closer look, this result may provide preliminary evidence for a mechanistic link for previous conflicting study results 13.…”
Section: Discussioncontrasting
confidence: 43%
“…In the light of previous reports showing that treatment with n3‐PUFAs improves left ventricular function in HF by reducing ventricular remodelling and myocardial fibrosis,8, 11 our finding is rather surprising at first. However, upon a closer look, this result may provide preliminary evidence for a mechanistic link for previous conflicting study results 13.…”
Section: Discussioncontrasting
confidence: 43%
“…In a recent study, EPA and DHA have been shown to reduce myocardial fibrosis. EPA and DHA supplementation for 6 months in post–myocardial infarction patients was associated with a favorable effect on left ventricular remodeling and a significant reduction in noninfarct myocardial fibrosis measured by cardiac magnetic resonance imaging (mean reduction, −5.6%; 95% CI, −10.4% to −0.9%; P =0.022) compared with placebo 35. In a subset of 6 patients from the current study, several resolvins, which have been shown to be present in healthy subjects,36, 37, 38 were absent or present at low levels in CAD patients not on omega‐3 ethyl‐ester; the resolvins were restored or their level increased in those receiving omega‐3 ethyl‐ester 39.…”
Section: Discussionmentioning
confidence: 96%
“…1 Dr. Naegele expressed concern regarding the safety of omega-3 fatty acids based on the numbers of mortality cases in the omega-3 fatty acid and placebo treatment arms. Dr. Naegele postulated that the long term cumulative effect of omega-3 fatty acids exposure may be harmful due to “lipid peroxidation” following “gradual accumulation within biological membranes.” Although, at the present time, the effects of omega-3 fatty acids on lipid peroxidation and mitochondrial glucose utilization remain unclear, 2 we do not find supportive evidence that indicate harmful effects from omega-3 fatty acids in our study.…”
Section: Lettermentioning
confidence: 99%
“…1 This was in part complicated by the heterogeneity in study methods and target patient populations in the medical literature. Our study results demonstrated substantial reductions in adverse left ventricular (LV) remodeling, non-infarct myocardial fibrosis, and circulating biomarkers of inflammation in those patients who achieved a substantial increase in RBC omega-3 fatty acid levels.…”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation